A survey on IP-based wireless sensor networks solutions - Rodrigues, Joel (2014)
Wireless sensor networks can be composed of thousands of smart sensing nodes that capture environment data in a cost-efficient way. Such networks present new challenges when compared to traditional computer networks, namely in terms of smart node processing power and very limited energy resources. Ubiquitous computing can benefit from wireless sensor networks, from the perspective that sensed data can be used on behalf of the user without explicit intervention, turning ubiquitous computing into a reality. For the data to be available everywhere wireless sensor networks must be connected to the Internet. Two main approaches can be considered: proxy-based or sensor node stack based. This second approach turns sensors into data producing hosts, also know as ”The Internet of Things”. For years the TCP/IP protocol suite was considered inappropriate for wireless sensor networks, mainly due to the inherent complexity and protocol overhead for such limited hardware. However, recent studies made connecting wireless sensor to the Internet possible for integration on the future Internet. This paper surveys the current state-of-the-art on the connection of wireless sensor networks to the Internet, presents related achievements, and provides insights on how to develop Internet Protocol-based communication solutions for wireless sensor networks today.